A rapid response and treatment service for care homes: a case study. (2nd January 2021) - Waldon, Mandy
Abstract : Rapid response services provide opportunities for older people living with frailty to remain in their own homes during an episode of deteriorating health. The government has announced additional funding to increase capacity and responsiveness for these services through the Ageing Well programme as part of the NHS Long Term Plan. Older people living with frailty are particularly at risk of the adverse effects of a hospital admission and evidence is emerging of the benefits of enhanced healthcare support to allow them to remain in their own home. The Hospital at Home model offers short-term, targeted interventions at acute hospital level care that can provide a truly person-centred experience within the home. This article describes a Rapid Response and Treatment service for older people living in care homes in Berkshire West and shares Sid's story to demonstrate how such a service is delivered. The COVID-19 pandemic has presented additional challenges and opportunities that highlight the ongoing need for the development of services that will support older people to prioritise what matters to them most.